Typhlocarcinus kerala, a new species of rhizopine crab from southwestern India, and the identity of T. craterifer Rathbun, 1914 (Crustacea: Brachyura: Pilumnidae) - Ng, Peter K. L.; Devi, Suvarna; Kumar, Appukuttannair Biju (Zootaxa, 2017)
A new species of rhizopine crab of the genus Typhlocarcinus Stimpson, 1858 (family Pilumnidae), is described from southwestern India. Typhlocarcinus kerala sp. nov. is characterised by its granular carapace with the dorsal regions well demarcated and the gastro-cardiac grooves deep, the anterolateral margin entire and prominently granulated, the posterolateral margin lacks a low granulated lobe, proportions of the ambulatory legs and shape of the female telson.